Experience in Managing a Complex Case of Infected Achilles Tendon Rupture with Segmental Loss: A Case Report - Ahmad-Ismani MS; Chong JS; Hj-Salleh MA; Ayeop MAS; Che-Ahmad A (Malaysian Orthopaedic Journal)
The Achilles tendon rupture often present as a significant clinical challenge. We present a complex case of chronic Achilles tendon rupture complicated by infection and segmental loss after failed primary repair. The patient underwent meticulous debridement, reconstruction using Baker's U-lengthening technique with augmentation using plantaris tendon. Tension-relieving sutures and a biosynthetic graft [Artelon® Flexband] were used for enhanced support. Post-operatively, a structured rehabilitation program was implemented, leading to successful healing with full weight-bearing capability at 12 weeks, with improved ankle function and no evidence of contracture. The utilisation of Baker's U-lengthening, along with adjunctive measures, proved effective in managing this challenging case. This report highlights the importance of a multidisciplinary approach, incorporating orthopaedic, infectious disease, and rehabilitation specialists in the comprehensive management of complex Achilles tendon injuries.